8-oxo-dG Levels in Gingival Crevicular Fluid and Increased Micronuclei Number as Markers of Panoramic Radiation Exposure - Shantiningsih, Rurie Ratna; Gracea, Rellyca Sola; Diba, Silviana Farrah; Yanuaryska, Ryna Dwi (Universiti Putra Malaysia Press, 2022)
Introduction: Micronuclear formation is possibly related to the increased levels of 8-oxo-dG, which is a DNA damage. Micronuclei is used as a biomarker of genotoxic damage due to panoramic radiographic exposure. The 8-oxo-dG levels detected in gingival crevicular fluid (GCF). This study aimed to determine the correlation of 8-oxo-dG levels in GCF with an increase in the number of micronuclei as the parameter of the effects of panoramic radiographic exposure. Methods: Randomized sampling was applied to 10 patients for each digital and conventional technique, indicated as the panoramic radiographic exposure at the radiology installation of RSGM UGM Prof. Soedomo. Smears on the gingival mucosa of each subject were obtained before exposure and 10 days after exposure, then stained via the Feulgen–Rossenbeck-modified method. Samples of GCF was acquired before and shortly after exposure to measure 8-oxo-dG levels by enzyme-linked immunosorbent assay (ELISA). Data were analyzed statistically with paired t-test and Pearson correlation test. Results:The 8-oxo-dG levels increased after the panoramic radiographic exposure in conventional and digital techniques. However, paired t-test showed no significant difference (p > 0.05). In addition, the 8-oxo-dG levels were significantly correlated (p < 0.01) with the increased number of micronuclei (r = 0.749). The correlation of digital techniques (r = 0.879) was higher than that of analog techniques (r = 0.673). Conclusion: The 8-oxo-dG levels in GCF increased because of panoramic radiographic exposure and correlated with the increased number of micronuclei in the gingival mucosa, as shown in conventional and digital radiographs.